Microbial cooperation improves bioleaching recovery rates - Corbett, Melissa; Watkin, Elizabeth (2019)
Whilst bioleaching is primarily used to recover minerals from low-grade ores, the increasing demand for Rare Earth elements combined with supply chain concerns is opening up new avenues of extraction from mine tailings, waste products and recyclable materials. Exploration of new, novel and economically viable techniques are required to manage the coming shortage and volatility of global markets with more environmentally sound alternatives to traditional mining operations holding the key.